2009
DOI: 10.1155/2009/174657
|View full text |Cite
|
Sign up to set email alerts
|

The 5-Lipoxygenase as a Common Pathway for Pathological Brain and Vascular Aging

Abstract: Epidemiological studies indicate age as a strong risk factor for developing cardiovascular and neurodegenerative diseases. During the aging process, changes in the expression of particular genes can influence the susceptibility to these diseases. 5-Lipoxygenase (5-LO) by oxidizing fatty acids forms leukotrienes, potent mediators of oxidative and inflammatory reactions, two key pathogenic events in both clinical settings. This enzyme is widely distributed in the cardiovascular as well as in the central nervous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Interestingly, post-mortem studies have shown that 5LO levels are upregulated in AD and PSP patients, as well as in relevant mouse models of AD and other tauopathies in areas of the brain more vulnerable to neurodegeneration, such as cortex and hippocampus [5, 3335]. Following this discover, in recent years, our group has demonstrated that 5LO is a key player in the development of the full pathological phenotype of these neurodegenerative disorders [7, 8].…”
Section: Tau and Tauopathiesmentioning
confidence: 99%
“…Interestingly, post-mortem studies have shown that 5LO levels are upregulated in AD and PSP patients, as well as in relevant mouse models of AD and other tauopathies in areas of the brain more vulnerable to neurodegeneration, such as cortex and hippocampus [5, 3335]. Following this discover, in recent years, our group has demonstrated that 5LO is a key player in the development of the full pathological phenotype of these neurodegenerative disorders [7, 8].…”
Section: Tau and Tauopathiesmentioning
confidence: 99%
“…5LO is found throughout the central nervous system, in both neuron and glia cells [17]. However, its expression levels are highest in the cortex and hippocampus areas, two regions that are particularly vulnerable to neurodegenerative insults [18, 19].…”
Section: -Lipoxygenase Pathway In Brain Aging and Alzheimer’s Diseasementioning
confidence: 99%
“…Since aging is one of the strongest risk factors for developing AD [17], initially it was proposed that this pathway could potentially be involved in brain aging and events germaine to the pathogenesis of AD [22]. Post-mortem studies have shown that compared with healthy controls, post-mortem AD brains had higher 5LO protein levels in cortex and hippocampus.…”
Section: -Lipoxygenase Pathway In Brain Aging and Alzheimer’s Diseasementioning
confidence: 99%
“…Several lines of research have established the presence of the 5-lipoxygenase (5-LOX; EC 1.13.11.34) pathway in the central nervous system (CNS) (Chinnici et al, 2007; Chu and Praticò, 2009; Lindgren et al, 1984; Miyamoto et al, 1987; Ohtsuki et al, 1995). Information about the site and the cell types responsible for the synthesis of 5-LOX products, the inflammatory leukotrienes and the anti-inflammatory lipoxins (Radmark et al, 2007, Serhan et al, 2008) in the CNS points to brain region differences in leukotriene formation (Chinnici et al, 2007; Miyamoto et al, 1987) and indicates the possibility of transcellular biosynthesis of cysteinyl leukotrienes in neuronal and glial cells (Farias et al, 2007).…”
mentioning
confidence: 99%